Association between ischemic heart disease and dietary intake of lycopene: a case–control study - Amjadi, Arezoo; Alami, Farkhondeh; Mohammadian, Mohammad Keshavarz; Mirshafaei, Seyed Reza; Azaryan, Fatemeh; Houshiar-Rad, Anahita; Esmaeili, Mina; Shekari, Soheila; Abdollahi, Morteza; Khoshdooz, Sara; Ajami, Marjan; Doaei, Saeid; et al. (Frontiers in Nutrition, 2024)
The effect of dietary lycopene on ischemic heart disease (IHD) is not clear. Hence, this study aimed to determine the association between dietary lycopene and IHD.Methods: This case-control study was conducted on 443 patients with physician confirmed diagnosis of IHD as the case group and 443 healthy individuals as the control group. Data on demographic, medical history, anthropometric, and physical activity of the participants were collected. Food intake was evaluated using a 237-item semi-quantitative food frequency questionnaire (FFQ). The dietary intake of lycopene was assessed using Nutritionist IV software.Results: A negative association was found between IHD and lycopene (OR: 0.98, CI 95%: 0.963-0.996, p=0.02). The results remained significant after adjustment for age and sex, additional adjustment for dietary intake of calorie and fat, further adjustments for BMI, and additional adjustment for smoking, drinking alcohol, and physical activity. The risk of IHD in people with the highest quartile of dietary intake of lycopene was significantly lower than those with the lowest quartile (OR=0.67, CI 95%: 0.46-0.97, P=0.036).There was a significant inverse relationship between intake of lycopene and IHD.Further prospective studies in different populations are required to elucidate the roles of lycopene against IHD.